2022
DOI: 10.21138/bage.3222
|View full text |Cite
|
Sign up to set email alerts
|

Distribución de especies cinegéticas en los espacios adehesados de Extremadura: comparativa entre el siglo XVIII y los cotos de caza mayor actuales

Abstract: Durante el siglo XVIII la caza mayor era una práctica reservada a las clases sociales dominantes, por razones de prestigio y distinción frente al resto de personas. No obstante, este modelo cinegético compartía protagonismo con otros tipos de caza en los que se perseguían fines diferentes. Bajo estas premisas, el objetivo de este trabajo es doble. Por una parte, analizar la distribución territorial de las especies de caza mayor a finales del siglo XVIII, basándose en los datos aportados por una fuente históric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…To do this, it is necessary to know the characteristics and needs in demand. The work carried out by Martín et al [24] showed the interest of hunting tourists in complementary activities other than hunting during their hunting trips, a situation which can also be seen in the study area. However, there are differences in terms of the characteristics of the trip between the general situation in Extremadura as a whole and that obtained for the study area.…”
Section: Hunting Tourismmentioning
confidence: 57%
See 3 more Smart Citations
“…To do this, it is necessary to know the characteristics and needs in demand. The work carried out by Martín et al [24] showed the interest of hunting tourists in complementary activities other than hunting during their hunting trips, a situation which can also be seen in the study area. However, there are differences in terms of the characteristics of the trip between the general situation in Extremadura as a whole and that obtained for the study area.…”
Section: Hunting Tourismmentioning
confidence: 57%
“…The development of hunting tourism is conditioned by the presence of hunting species of interest to hunters that have the capacity to attract chasers due to their uniqueness and hunting values in a given territory. For this reason, and given that big game species are those of greatest interest to hunting tourists [24,43], it was considered necessary to carry out a specific analysis of the distribution of these species in the dehesa reserves located in the study area. In this sense, Figure 5 shows the undoubted hunting values present in the study area, where we can observe the great extension of the main big game species distributed throughout this territory, except in the case of the mountain goat (Capra pyrenaica).…”
Section: Hunting Resourcesmentioning
confidence: 99%
See 2 more Smart Citations